Le positionnement des villes belges dans le réseau global des services avancés - Laurent Aujean; Etienne Castiau; Marcel Roelandts; Christian Vandermotten (Belgeo)
Starting from the concepts and methods developed by research on global cities networks, this article aims at presenting a new Belgian urban hierarchy, based on the analysis of the presence of advanced production services firms.About ten major urban centres have been selected (with particular attention to the Brussels-Capital Region and its highly dynamic Flemish periphery around Zaventem) and their connection level assessed from a national and international point of view.Aside from Brussels’ (and to a lesser extent Antwerp’s) predominance, the positions of some Belgian cities appear amazing. Moreover, the hierarchy changes according to level (national or international connectivity) and sector. This helps to understand Belgian cities’ connections, both at national and international level, as well as the new geographical division of labour in the distribution of advanced services.